Communication and sport: a call to action - Salgado, Paulo (2021)
The economic influence of media has dramatically changed the world of sport, leading sports organisations to increase their focus on communication and assets like brands and reputation. The intent for a more strategic communication within the sports industry must consider a broader and more profound reflection of how the world of sports intertwines with communication and its interactive process of creation, selection, and retention of meaning (Weick, 1979). As a practice and as a business, the social role played by sports, and the singularities of sports organisations are central pieces for the comprehension of the strategic sports communication model presented in this paper. It aims at encouraging researchers to dive into the realm of sports communication.